Crystallization history of Oligocene ijolitic rocks from the Doupovske hory Volcanic Complex (Czech Republic) - Haloda,J.; Rapprich,V.; Holub,F.V.; Halodova,P.; Vaculovic,T. (Journal of Geosciences, 2010)
Ijolitic rocks of the Flurbuhl Composite Intrusion rank to the most primitive intrusive rocks found within the Doupovske hory Volcanic Complex. Studies of mineral chemistry together with crystallization modelling of melteigite and ijolite brought new information about the evolution of ijolitic magmas and their ascent. Crystallization modelling affirms the absence of accumulated minerals and confirms that the recalculated major-element bulk-rock analyses reflect the compositions of their original parental magmas accurately. Melteigite crystallized by early equilibrium crystallization under pressure of approximately 4 kbar (estimated minimum cooling rate is ˜0.02 °C/hr) and subsequent fractional crystallization under much lower pressure (˜0.2 kbar). Ijolite originated by fractional crystallization of a slightly more evolved magma batch under lower pressures probably at the final emplacement level. The results of crystallization modelling and estimates of REE contents in parental melts suggest a close genetic relationship between both rock suites. The olivine-bearing melteigite was postulated as a possible parental magma composition for derivation of the olivine-free ijolite.
Keywords: Nephelinolite; melteigite; ijolite; crystallization modelling; fractional crystallization; Doupovske hory Mts.